(untitled) (Journal of Engineering, 2018)
Buzurgan oil Field which is located in south of Iraq has been producing oil for five decades that caused production to drop in many oil wells. This paper provides a technical and economical comparison between the ESP and gas lift in one oil well (Bu-16) to help enhancing production and maximize revenue. Prosper software was used to build, match and design the artificial lift method for the selected well, also to predict the well behavior at different water cut values and its effect on artificial lift method efficiency. The validity of software model was confirmed by matching, where the error difference value between actual and calculated data was (-1.77%). The ESP results showed the durability of ESP regarding the increment of water cut value, on the other hand Gas lift design was restricted to surface injection pressure and injected gas volume which in return causes a restriction to production rate specially when water cut value increases. Economically the results showed ESP is cheaper and more applicable than gas lift.